2010
DOI: 10.1002/jemt.20845
|View full text |Cite
|
Sign up to set email alerts
|

Cellular uptake pathway and drug release characteristics of drug‐encapsulated glycol chitosan nanoparticles in live cells

Abstract: Herein, we evaluated the cellular uptake pathways of hydrophobically modified glycol chitosan (HGC) nanoparticles as nano-sized drug carriers using cellular imaging technology. The endocytic pathway of nanocarriers for intracellular drug delivery is of great interest for the design of high efficacy delivery carriers for therapeutic agents. To evaluate the cellular uptake pathways of HGC nanoparticles, HGC was chemically labeled with near infrared (NIR) fluorescence dye, Cy5.5, to visualize the nanoparticle und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…Endocytosis is the primary mechanism for movement of extracellular material across biological membranes (11) .…”
Section: Endosomal Escapementioning
confidence: 99%
See 1 more Smart Citation
“…Endocytosis is the primary mechanism for movement of extracellular material across biological membranes (11) .…”
Section: Endosomal Escapementioning
confidence: 99%
“…If internalization is by endocytosis, as is predominantly the case, the objective is to escape the endosome, otherwise the genetic material will be degraded and expelled via a lysosome (11) . If endosomal escape is successful then the DNA must be delivered to the nucleus where it can finally exact a sustained therapeutic effect (12) .…”
Section: Introductionmentioning
confidence: 99%
“…The surface of nanoparticles is commonly coated with a layer of dissolved extracellular molecules in body fluids, such as proteins, sugars and lipids before their encounter with the cellular membranes, the so‐called protein corona . When reach the site of action, the loaded cargo may be released outside or cells take up nanoparticles and unload cargo at the desired intracellular compartment . Generally, the transport of macromolecular carriers such as nanoparticles from the cell surface to the lysosomal vesicles occurs with a process known as endocytosis .…”
Section: Introductionmentioning
confidence: 99%
“…It was also clearly observed that the accumulation of nano-particulates in tumor cells was higher than that in normal fibroblast cells, suggesting potentially more efficient tumor targeting. The enhanced cellular uptake of the chitosan-conjugated nano-carrier used as a vehicle of IONP might result from several endocytotic pathways, as previously reported [37,38]. Therefore, the result of an enhanced cellular uptake of IONP a b c d e by loading them into the nano-carrier supported the use of the IONP-loaded nano-carrier as an in-vivo MRI probe for tumor tissues.…”
Section: Mr Contrast Effect and Cellular Uptake Of Ionp-loaded Nano-cmentioning
confidence: 68%